Cicha rozmowa ostatnich przekładów Tonego Pretnara / The quiet conversation of Tony Pretnar’s last translation - Šurla, Andrej (Przekłady Literatur Słowiańskich, 2009)
The volume of poems translated by Tony Pretnar I Whisper to you (1992) written by poets of different historical and literary periods clearly reveals the personal dialog of the translator with literature. The personal experience of the translator had the influence on the choice of the poems. The subject of his „diary of translation” is isolation, feeling of deficiency (Szymborska, Orkan), death (Szymborska, Bursa), the crisis of expression (Wojaczek). However, it seems that the definite expression of Pretnar’s translation is optimistic. A chance to overcome death he sees in a creative act. (also „quiet conversation” of Wojaczek in spite of his doubt in the power of word expression stands a poetical witness in sense of life) and in religions experience (Wat, Staff, Gałczyński). The most everlasting confirmation of eternity for Pretnar were love and contiguity to another human being (Krasiński, Przybora).